2017
DOI: 10.1515/soeu-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Effects of Emigration and Remittances in the Western Balkans. A Forecasting Based on a Delphi Process

Abstract: The objective of this paper is to forecast the size and effects of remittances and emigration in four Western-Balkan countries: Macedonia, Albania, Serbia and Kosovo, through application of a qualitative forecasting method: a Delphi questionnaire. We solicited consensus building within and between two groups of respondents: 10 experts and 20 receivers were consulted per country in three subsequent rounds -two on the same group, and a third cross-round whereby average answers of receivers were given to experts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…After the outbreak of the crisis, the average annual decline of remittances received in SEE6 has been 1.8%, with differences across countries. Hence, while remittances to SEE countries have remained relatively stable, contrary to expectations, they turned out to be procyclical (Petreski et al 2017).…”
Section: Literature Reviewmentioning
confidence: 66%
“…After the outbreak of the crisis, the average annual decline of remittances received in SEE6 has been 1.8%, with differences across countries. Hence, while remittances to SEE countries have remained relatively stable, contrary to expectations, they turned out to be procyclical (Petreski et al 2017).…”
Section: Literature Reviewmentioning
confidence: 66%
“…The size and effects of remittances and emigration and their impact on poverty are analyzed on a sample of four Western Balkan countries: Macedonia, Albania, Serbia and Kosovo, and the conclusion is that while remittances will increase, emigration will show a slight decrease, but the level of poverty can be reduced by remittances [42].…”
Section: Methodsmentioning
confidence: 99%
“…However, a newer stability concern emerged in 2015 in the shape of rapidly increasing migration. The issue arose in the five Western Balkan states -Kosovo was still negotiating theirs at the time of writingthat had signed visa-free travel agreements with the EU (Petreski et al 2018). In 2015, the European Commission reported that the number of asylum applications submitted in EU and Schengenassociated countries by nationals of the five visa-free Western Balkan countries was rising steadilythere had been 53,705 applications in 2013, but their number had risen by 40% in the first nine months of 2014 (European Commission 2015).…”
Section: Phase Three: From Croatia's Accession Until the Unveiling Ofmentioning
confidence: 99%